2017
DOI: 10.1007/s11056-017-9591-7
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of European larch (Larix decidua Mill.) forests to wildfires in the western Alps

Abstract: European larch is a dominant species in the subalpine belt of the western Alps. Despite recent increases in wildfire activity in this region, fire ecology of European larch is poorly understood compared to other larch species around the world. This study aims to assess whether European larch forests are resilient to fires, and to find out the factors that drive such resilience. We assessed the recovery of larch forests along a gradient of fire severity (low, moderate, high) based on the abundance and dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 81 publications
1
25
0
1
Order By: Relevance
“…, Moris et al. ), and fires are expected to increase in frequency and intensity with future warmer and drier conditions (Schumacher and Bugmann , Dupire et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Moris et al. ), and fires are expected to increase in frequency and intensity with future warmer and drier conditions (Schumacher and Bugmann , Dupire et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we aim to investigate patterns of variation of fire resistance traits from individuals to biogeographic regions across the wide climatic and vegetation gradients of the western Alps. Alpine forests are mostly prone to surface fires (Genries et al 2009, Moris et al 2017, and fires are expected to increase in frequency and intensity with future warmer and drier conditions (Schumacher andBugmann 2006, Dupire et al 2017). Paleoecological analyses have shown longterm differences in fire activity between species and plant communities in the Alps (Tinner et al 2000, Blarquez et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, lighting represented on average 33 % of all summer ignitions among those with a known cause and 38 % between June and August (comparable to other Alpine regions, e.g., 40 % in Austria; Müller et al, 2012). Such a high rate is indicative of the fact that summer fires in this study area can still be considered a partially "natural" disturbance regime, except for the fact that suppression policies are still quite aggressive and prevent a more complete restoration of fire as an agent potentially useful for regeneration and ecosystem functioning (Vazquez Moris et al, 2017). In turn, in the study area the frequency of lightning-induced fires is highly correlated with the summer Standardized Precipitation and Evaporation Index in Aosta (Castagneri et al, 2015) (R = 0.55 for all months between May and September and 0.69 for the month of July).…”
Section: Natural Drivers Of Fire Ignitionmentioning
confidence: 75%
“…Historically, some ecosystems such as forests dominated by Scots pine or European larch might have evolved under medium-to high-frequency fire regimes (Vazquez Moris et al, 2017). However, the frequency and severity of fires have been heavily influenced by human activities, such as widespread pastoral fires and a century-long strict fire suppression policy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forest management and human actions may strongly influence the spatiotemporal pattern of fire ignitions (DeWilde and Chapin, 2006), especially in highly developed regions such as southern Europe, where most of the wildland fires are human-induced. Here, several studies have shown the significance of the distance of forest fires to roads, settlements, and infrastructure or specific land uses or even its abandonment as predisposition for fire ignition (Vega-Garcia et al, 1995;Goldammer, 2003;Catry et al, 2009;Martinez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%